A wicca no Brasil : adesão e permanência dos adeptos na região metropolitana do Recife - Bezerra, Karina Oliveira (2012)
The Wicca religion began in the 1950s of the twentieth century in England and has since spread to several other countries, in which Brazil is included, where the movement wiccan is consolidated - although it is little known and even less studied. The knowledge of their social dynamics opens interesting perspectives for the understanding of new religious movements in Brazil. This paper seeks, then, to identify among the practitioners of Wicca, the Metropolitan Region of Recife, both solitary and group members, the means by which, and the motivations that led them to enter and remain in the religion. To this was done a study of the historical development of Wicca in England and the United States, a Wicca documentary research in Brazil, and an oral history and phenomenological description of the Wiccan movement in Greater Recife. Forty questionnaires were applied and made four interviews. The interpretation of data obtained in the literature, documents, interviews and questionnaires relied on the concept of "rational choice", developed in the sociology of religion, Stark and Bainbridge